Sliding Mode Control for Longitudinal Aircraft Dynamics - Iskrenovic-Momcilovic, Olivera (Journal of Automation, Mobile Robotics and Intelligent Systems, 2018)
The control of the longitudinal aircraft dynamics is challenging because the mathematical model of aircraft is highly nonlinear. This paper considers a sliding mode control design based on linearization of the aircraft, with the pitch angle and elevator deflection as the trim variables. The design further exploits the decomposition of the aircraft dynamics into its short-period and phugoid approximations. The discrete-time variable structure system synthesis is performed on the base of the elevator transfer function short-period approximation. This control system contains a sliding mode controller, an observer, based on nominal aircraft model without finite zero and two additional control channels for the aircraft and for the aircraft model. The realised system is stable and robust for parameter and external disturbances.